On Jacobson Radical of Ternary Γ-Semirings - Liu, Yang; Munir, Mohammad; Kausar, Nasreen; Xu, Qingbing (SOUTHEAST ASIAN MATHEMATICAL SOC-SEAMS, 2024)
In this article, we first introduce the concept of a new type of Jacobson radical of a ternary Gamma-semiring T which is defined by semiregularity. Several characterization theorems of this type of Jacobson radical are given.
Keywords: Jacobson radical; Ternary Gamma-semiring; Semi-regularity; Mathematics